PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN DIBURSA EFEK INDONESIA TAHUN 2010-2014 - Atikah Mustika; Rina Tjandrakirana DP; Ika Sasti Ferina (AKUNTABILITAS, 2015)
This study aims to determine the influence of Intellectual Capital on Financial Performance of Banking Company in Indonesia. This study uses a Pulic Method (VAICTM) in measuring the performance of Intellectual Capital separately-using Human Capital Efficiency, Structural Capital Efficiency , Capital Employed Efficiency, or aggregately –using Value Added Intellectual Coefficient. ROA (Return on Asset)is a proxy of financial performance as the dependent variable.Purposive sampling method is used to determine the samples of this study.There are 12 banking companies that are listed in Indonesia Stock Exchange from 2010 to 2014.Results showed that simultaneously there is significant influence between Human Capital Efficiency, Structural Capital Efficiency, Capital Employed Efficiency and Value Added Intellectual Coefficient with ROA. However, if the measurements performed on the components of VAICTM (HCE,SCE and CEE) then only Structural Capital Efficiency , Capital Employed Efficiency and Value Added Intellectual Coefficient that have positive and significant influence on ROA.